Filling ecological gaps in Chilean Central Patagonia: Patterns of biodiversity and distribution of sublittoral benthic invertebrates from the Katalalixar National Reserve waters (∼48°S) - Zapata-Hernandez, German; Gorny, Matthias; Montiel San Martin, Americo Manuel (My University, 2022)
Knowledge about the composition, diversity, and geographic distribution of marine species is important for successful conservation planning in the future. The ecological and zoogeographic patterns of benthic communities in Central Patagonia have been scarcely studied, due to the remoteness of the area combined with harsh weather conditions. During the past years, five scientific expeditions were executed in order to study the biodiversity, ecological, and biogeographical patterns of benthic invertebrates in the Katalalixar National Reserve (KNR) waters, Central Patagonia (similar to 48 degrees S). Our analyses comprised images from 26 video transects using a remotely operated vehicle, completed with biological sampling at four stations by means of SCUBA diving, covering a bathymetric range from 10 to 220 m depth. Stations covered the entire longitudinal range of the KNR, from inner channels to the Pacific Ocean. A total of 187 benthic invertebrate taxa were identified as OTUs (operational taxonomic units), with mollusks being the most conspicuous taxonomic group (18.7%), followed by sponges, echinoderms (16.6% each), and arthropods (14.4%). A higher OTU richness (42 to 51 OTUs) was observed in the central and western parts of the KNR waters. Analyses of the beta-diversity indicated a similar level of species turnover between shallow, intermediate, and deep strata, as well as an important turnover between different locations. Dissimilitudes in the assemblage structure of invertebrates were explained mainly by changes in substrate types and longitude. Most of the species (49%) found in the KNR waters showed a wide latitudinal distribution range along the Eastern South Pacific Ocean (ESP) and the Chilean Patagonia of fjords and channels (CPFC) (similar to 18 degrees S and similar to 56 degrees S), whereas 9.4% of the species have a wide distribution range between the CPFC and south of the Antarctic polar front (SAPF) (similar to 42 degrees S and similar to 65 degrees S). Since only 16.7% of the species identified in the KNR are distributed exclusively in CPFC waters, it may be considered a transition area for marine invertebrates. It is distributed between northern ESP and SAPF. Knowledge of species composition and distribution patterns along spatial and environmental gradients is essential for any sustainable management, monitoring, and future conservation plans to protect the fragile and diverse marine ecosystems of Chilean Patagonia.
Keywords: marine biodiversity; sublittoral benthos; zoogeography; channels and fjords; chilean patagonia; remotely operate vehicle; species turnover